2020
DOI: 10.1186/s13071-020-04066-6
|View full text |Cite
|
Sign up to set email alerts
|

A standardised method of marking male mosquitoes with fluorescent dust

Abstract: Background: Prior to a major release campaign of sterile insects, including the sterile insect technique, male mosquitoes must be marked and released (small scale) to determine key parameters including wild population abundance, dispersal and survival. Marking insects has been routinely carried out for over 100 years; however, there is no gold standard regarding the marking of specific disease-transmitting mosquitoes including Anopheles arabiensis, Aedes aegypti and Aedes albopictus. The research presented off… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Most agricultural pest control programs release color-marked insects to distinguish sterile males during field monitoring and in MRRs [130]. This is not ideal for mosquitoes because the fluorescent color might create anxiety in people.…”
Section: Marking Mosquitoesmentioning
confidence: 99%
“…Most agricultural pest control programs release color-marked insects to distinguish sterile males during field monitoring and in MRRs [130]. This is not ideal for mosquitoes because the fluorescent color might create anxiety in people.…”
Section: Marking Mosquitoesmentioning
confidence: 99%
“…aegypti [ 10 ], An. arabiensis [ 28 ], and Psorophora mosquitoes [ 26 ], where transference occurred from marked males to unmarked females, from marked males to both males and females, and from marked to unmarked individuals in a confined space, respectively. Differences in study findings, like a higher amount of powder transfer in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Powder transference between different sex individuals and during copulation has been observed when placing equal numbers of Drosophila pseudoobscura dusted nonvirgin males and females; some genital transfer if nonvirgin individuals were allowed to clean themselves before mixing them under moderately crowded conditions; and no transfer during mating of virgin adults [ 6 ]. Studies using Anopheles arabiensis found that males are capable of transferring the mark, only detectable when examined under a stereoscope, to both males and females and that this transference increased over time [ 28 ], but no powder transference among adult mosquito mating pairs was found using Culex quinquefasciatus marked males and unmarked females [ 29 ]. Transference between marked males to unmarked females was also reported when using fluorescent powders in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…A method was developed for marking ~70,000 sterile chilled male mosquitoes in 20 min [ 317 ]. This approach was integrated into protocols to conduct mark-release-recapture experiments allowing the estimation of their survival, dispersal and competitiveness [ 318 ].…”
Section: Main Research Achievements—human Disease Vectorsmentioning
confidence: 99%